Inhibition of Nkcc1 promotes axonal growth and motor recovery in ischemic rats. (4th December 2017) - Mu, X.P.; Wang, H.B.; Cheng, X.; Yang, L.; Sun, X.Y.; Qu, H.L.; Zhao, S.S.; Zhou, Z.K.; Liu, T.T.; Xiao, T.; Song, B.; Jolkkonen, J.; et al.
Highlights: Bumetanide promoted axonal growth after cerebral ischemia in rats. Bumetanide upregulated KCC2, BDNF, downregulated NKCC1, NogoA after stroke in rats. Bumetanide improved behavioral outcome after cerebral ischemia in rats. Abstract: Bumetanide is a selective inhibitor of the Na + -K + -Cl − -co-transporter 1(NKCC1). We studied whether bumetanide could affect axonal growth and behavioral outcome in stroke rats. Adult male Wistar rats were randomly assigned to four groups: sham-operated rats treated with vehicle or bumetanide, and ischemic rats treated with vehicle or bumetanide. Endothelin-1 was used to induce focal cerebral ischemia. Bumetanide administration (i.c.v.) started on postoperative day 7 and continued for 3 weeks. Biotinylated dextran amine (BDA) was injected into the right imotor cortex on postoperative day 14 to trace corticospinal tract (CST) fibers sprouting into the denervated cervical spinal cord. Nogo-A, NKCC1, KCC2 and BDNF in the perilesional cortex and BDA, PSD-95 and vGlut1 in the denervated spinal cord were measured by immunohistochemistry and/or Western blot. Behavioral outcome of rats was assessed by the beam walking and cylinder tests. The total length of CST fibers sprouting into the denervated cervical spinal cord significantly increased after stroke and bumetanide further increased this sprouting. Bumetanide treatment also decreased the expressions of NKCC1 and Nogo-A, increased the expressions of KCC2 and BDNF in the perilesional cortex and enhanced the synaptic plasticity in the denervated cervical spinal cord after cerebral ischemia. The behavioral performance of ischemic rats was significantly improved by bumetanide. In conclusion, bumetanide promoted post-stroke axonal sprouting together accompanied by an improved behavioral outcome possibly through restoring and maintaining neuronal chloride homeostasis and creating a recovery-promoting microenvironment by overcoming the axonal growth inhibition encountered after cerebral ischemia in rats.